Partial resistance of SARS-CoV-2 Delta variants to vaccine-elicited antibodies and convalescent sera - Takuya Tada (Elsevier, 2021)
Summary: Highly transmissible SARS-CoV-2 variants identified in India and designated B.1.617, Kappa (B.1.617.1), Delta (B.1.617.2), B.1.618, and B.1.36.29 contain spike mutations L452R, T478K, E484K, E484Q, and N440K located within the spike receptor-binding domain and thus could contribute to increased transmissibility and potentially allow re-infection or cause resistance to vaccine-elicited antibody. To address these issues, we used lentiviruses pseudotyped by variant spikes to measure their neutralization by convalescent sera, vaccine-elicited and Regeneron therapeutic antibodies, and ACE2 affinity. Convalescent sera and vaccine-elicited antibodies neutralized viruses with Delta spike with 2- to 5-fold decrease in titer in different donors. Regeneron antibody cocktail neutralized virus with the Delta spike with a 2.6-fold decrease in titer. Neutralization resistance to serum antibodies and monoclonal antibodies was mediated by L452R mutation. These relatively modest decreases in antibody neutralization titer for viruses with variant spike proteins suggest that current vaccines will remain protective against the family of Delta variants.